Integrated District Heating and Electric Power Plants - Zoega, Johannes (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1976)
The city of Reykjavik, Iceland, is planning to use a thermal field (Nesjavellir) some 30 Km from the city, to produce electricity as well as heat for district heating from deep wells already drilled. The inflow well temperature at 1800m is about 280C. As the borehole fluid contains various dissolved chemicals (minerals) that make it unfit for human consumption, it has been decided to use cold shallow ground water to be found in abundance in this field, and heat it using the hot borehole fluid. After heating this ground water above the boiling point, dissolved air is removed in de-aerators before the water is pumped to the city